ENHANCING AN ORGANIZATIONAL CHANGE: AN ANALYSIS OF FACTORS AFFECTING CHANGES IN SCHOOL ORGANIZATIONS - Abd. Qadir Muslim; Aulia Luqman Aziz (Universitas Brawijaya, 2019)
Organizational change is a phenomenon that must be faced and carried out by every individual to achieve organizational goals. Organizational change is required by every organization to maintain its existence amid competition and as a tool to achieve organizational goals. In addition, organizational change aims to improve the performance to be better. This study aims to create changes in school organization by analyzing the factors that influence better organizational change. This study was qualitative research which analyzes literature reviews related to organizational change. Considering the data analysis, this study used library research to examine the literature related to organizational change. This research was conducted on research results, library books, documents, and information contained on the internet. The data collected in this study were analyzed qualitatively by considering the research objectives. The results showed that the changes in school organization were caused by political practices, organizational learning, organizational culture, and principal leadership. The results showed that the changes in school organization were caused by political practices, organizational learning, organizational culture, and principal leadership. Therefore, leadership greatly influence the factors that can bring about organizational change.